Penggunaan Media Sosial Sebagi Strategi Komunikasi Pemasaran Masyarakat Di Kelurahan Pekayon Jaya Bekasi Selatan - mareta Puri Rahastine; Yulianti Fajar Wulandari (Jurnal Komunikasi, 2020)
The progress of Information Technology Communication (ICT) makes people have to develop along with the times, not a few people who use the internet, especially social media which is used as promotional media, of course, because of the vast reach and promotion costs needed are very cheap. This study uses a qualitative research method with a qualitative approach. The research was conducted to residents of RT 05, RW 13, Pekayon Jaya, South Bekasi Kelurahan. The results of the survey showed that there were many residents doing promotions with whatsapp group applications to sell their products, this can be seen from the number of residents uploaded every day.